AN ANALYSIS OF STUDENTS' UNDERSTANDING IN REVIEWING ARTICLES: CASE STUDIES AND THEIR PERSPECTIVE - Ruslan, Zuhra Adminira; Munawwarah, Munawwarah (Chimica Didactica Acta, 2025)
Literature review is the process of collecting, analyzing, and synthesizing information from various sources that are relevant to a particular research topic. These sources can be scientific journals, books, articles, research reports, or other credible sources. In college, the task of evaluating literature is very common. Students are often asked to conduct literature reviews as part of their coursework. This study aims to find out how students understand and carry out literature review tasks. For this reason, the researcher directly observed 4th semester students of Chemistry Education UNM who were working on literature review assignments. The researcher collected data from their assignments and also the results of the surveys they filled out. By analyzing this data, the researcher wanted to find out to what extent students understood this assignment, what difficulties they faced, and what they thought about the literature review assignment. The results of the study showed that students generally showed a very good category in using language according to writing rules. Meanwhile, for the level of understanding of the topic, completeness of literary sources, and analysis of literary content, they had shown a good category. However, in writing references to the results of the literature review, students only showed a sufficient category. The survey showed that the literature review assignment helped most students in analyzing information and finding relevant sources. However, many students have difficulty in grouping information, making in-depth conclusions, analyzing information, reading many articles, and understanding unfamiliar language. These difficulties make it difficult for test takers to focus on completing literature reviews. This indicates that lecturers need to improve the way they give literature review assignments and apply more effective teaching strategies to help students understand how to review literature well, so that students are more trained in critical and systematic thinking.